Experimental Study to Replace Conventional Bricks with Papercrete Bricks Incorporating Various Admixtures - Tarun Kumar; Varun Kumar; Sangam Kumar; Vikas; Ashish Juneja (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The study focuses on identifying suitable admixtures that can positively impact the workability, strength, and insulation capabilities of papercrete. Various types and concentrations of admixtures, such as fly ash, glass fiber, and glass powder, silica fumes, iron powder, jute fibre etc are introduced to the papercrete mix to assess their influence on the material's overall performance. The results of this study contribute to the broader goal of promoting sustainable construction practices by improving the performance and versatility of papercrete. By identifying effective admixtures, this study offers practical guidance for architects, engineers, and builders seeking environmentally friendly alternatives in the pursuit of more resilient and energy-efficient building materials.
Keywords: Fly Ash; Glass Fiber; Glass Powder; Silica Fumes; Iron Powder; Jute Fibre